Population Attributable Fraction of Ischemic Heart Disease Associated to Hypertension in the Middle East and North Africa - Marzieh Mirzajani; Masoud Mirzaei (Shahid Sadoughi University of Medical Sciences, 2015)
Background: Ischemic Heart Disease has been increasing in the Middle East and North Africa. Hypertension is an important modifiable risk factor of IHD and play an important role in the epidemic of IHD. Hypertension is responsible for about 45% of IHD mortality and affects more than one billion people around the world. Objective: This study aims to quantify the population attributable fraction of IHD due to hypertension in the Middle East and North Africa. Methods: Sex-specific prevalence of hypertension was obtained from national and international studies. Moreover, age-adjusted hazard ratio (HR) of IHD and hypertension was extracted from the Tehran Lipid and Glucose Study (TLGS). HR and sex-specific prevalence of hypertension were used to calculate PAF of IHD due to hypertension in various countries of the region. Results: The sex-specific prevalence of hypertension was available for seventeen countries of the region. Hypertension ranged from 4.5% in Palestine to 47% in Algeria in females and from 2.2%in Palestine to 50.7% in Oman in males. The fraction of IHD attributable to hypertension ranged from 4.3%in Palestine to 32%in Algeria in females and from 2.2% in Palestine to 33.7%in Oman males. Conclusion: Up to 33% IHD males mortality attributable to hypertension. It seems that hypertension is increasing in MENA and prevention programs is needed to control prevalence IHD.